1999
DOI: 10.1161/01.cir.100.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sympathetic and Ventilatory Responses to Central Chemoreflex Activation in Heart Failure

Abstract: Background-Sympathetic activation and respiratory abnormalities may each be implicated in the pathophysiology of congestive heart failure (CHF). Chemoreflexes are an important mechanism regulating both sympathetic drive and breathing. We therefore tested the hypothesis that chemoreflex function is altered in CHF. Methods and Results-We compared ventilatory, sympathetic, heart rate, and blood pressure responses to hypoxia, hypercapnia, and the cold pressor test in 9 patients with CHF and 9 control subjects matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
164
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(187 citation statements)
references
References 47 publications
14
164
2
7
Order By: Relevance
“…But the ventilatory response to isocapnic hypoxia, an index of peripheral chemoreflex function, in CHF patients seems less clear. Peripheral chemoreflex responses to hypoxia were not enhanced in patients with mild NYHA Class II-III CHF distinguished by dyspnea to mild (III) or moderate (II) exercise (Narkiewicz et al 1999). Similarly, other clinical studies (Haque et al 1996,van de Borne et al 1996 reported that suppression of peripheral chemoreceptor activity by hyperoxia had no effect on muscle sympathetic nerve activity or arterial pressure.…”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 62%
See 1 more Smart Citation
“…But the ventilatory response to isocapnic hypoxia, an index of peripheral chemoreflex function, in CHF patients seems less clear. Peripheral chemoreflex responses to hypoxia were not enhanced in patients with mild NYHA Class II-III CHF distinguished by dyspnea to mild (III) or moderate (II) exercise (Narkiewicz et al 1999). Similarly, other clinical studies (Haque et al 1996,van de Borne et al 1996 reported that suppression of peripheral chemoreceptor activity by hyperoxia had no effect on muscle sympathetic nerve activity or arterial pressure.…”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 62%
“…Several lines of evidence also make it clear that augmented excitatory reflexes further boost activation of sympathetic outflow in CHF. These reflexes encompass sympathetic excitatory cardiac (Wang et al 1999), somatic (Sinoway and Li, 2004), peripheral ,Sun et al 1999a) and central chemoreceptor reflexes (Narkiewicz et al 1999). …”
Section: Chemoreflex Control Of Sympathetic Function In Heart Failurementioning
confidence: 99%
“…Sympathetic activation has been implicated in the pathogenesis of hypertension, obstructive sleep apnea, and congestive heart failure. [1][2][3][4] In healthy humans, muscle sympathetic nervous activity (MSNA) varies widely across subjects but is relatively reproducible within the same individual. 5,6 The substantial between-subject variance in sympathetic traffic can be only partially explained by age, body mass index, blood pressure, reflex mechanisms, and genetic factors.…”
mentioning
confidence: 99%
“…2,3 The correlation between respiratory rate and sympathetic traffic may be, however, secondary to impairment of reflex mechanisms, or severity of heart failure, with consequent tachypnea, in patients with heart failure. 3,4 The relationship between spontaneous breathing rate and direct measures of sympathetic traffic in healthy humans has not been studied previously. We, therefore, tested the hypothesis that respiratory rate is linked to MSNA and chemoreflex sensitivity in normal subjects, independent of other variables, including age, body mass index, and blood pressure.…”
mentioning
confidence: 99%
“…The main variables assessed with this methodology are: peak oxygen consumption (VO 2 peak), VO 2 at the anaerobic threshold, oxygen pulse (PO 2 ), ΔVO 2 /Δload, relation between ventilation and carbon dioxide production (VE/VCO 2 Cardiopulmonary testing and left bundle branch block Int J Cardiovasc Sci. 2017;30(1): [11][12][13][14][15][16][17][18][19] Original Article slope) and VO 2 recovery kinetics. On the other hand, it has been documented that LVEF assessed through echocardiogram does not show a satisfactory relation to VO 2 , 5,6 and thus does not constitute a good predictor of functional capacity.…”
Section: Introductionmentioning
confidence: 99%